A Meta Analysis of Inductive Learning-Based Modules to Improve Critical Thinking Skills in Science - Nugroho, Anwari Adi; Wati, Widya; Ramli, Murni (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
Critical thinking skills in science learning can be improved by learning accompanied by learning model-based modules. Inductive learning is one of the lessons that can be integrated with the module as an alternative to empower critical thinking skills. This meta-analysis research aims to determine the effectiveness of learning with inductive learning-based modules to improve critical thinking skills, especially in the fields of science (biology, physics, and chemistry). This type of research was survey research and descriptive. Data were collected online and obtained 13 articles in the fields of biology, physics, and chemistry from 2014-2019 published in Indonesia and outside Indonesia. The calculation results show that the average effect size (ES) was 2.1 with the high category. These results indicate that science learning with inductive learning-based modules provides high effectiveness in improving critical thinking skills. Based on the relationship between variables, it was known that the variable in the field of study gives the greatest ES results (ES = 4.3) in the field of physics, while the variable for education level gives the largest ES result (ES = 2.14) at the high school level.